2018
DOI: 10.1038/s41598-018-20728-z
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanoparticles have lethal and sublethal adverse effects on development and longevity by inducing ROS-mediated stress responses

Abstract: Silver nanoparticles (AgNPs) are widely used in the household, medical and industrial sectors due to their effective bactericidal activities and unique plasmonic properties. Despite the promising advantages, safety concerns have been raised over the usage of AgNPs because they pose potential hazards. However, the mechanistic basis behind AgNPs toxicity, particularly the sublethal effects at the organismal level, has remained unclear. In this study, we used a powerful in vivo platform Drosophila melanogaster to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
114
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(122 citation statements)
references
References 87 publications
(79 reference statements)
6
114
0
2
Order By: Relevance
“…On the basis of these ndings, it was demonstrated that the concentration range from 10 to 100 mg L À1 of AgNPs-EW did not cause any signicant acute and chronic toxic effects on the reproductive traits, namely the fecundity, hatchability, viability, duration of development, and pigmentation of Drosophila. We compared these ndings with previously reported AgNPs toxicity studies on Drosophila and summarize the results in Table 2, [58][59][60][61][62] which clearly shows that AgNPs toxicity is based on the capping agents used for nanoparticles synthesis, size, and dose. Based on our literature study, we understand that this is the rst report of AgNPs-EW having no acute and chronic toxicity effects on Drosophila at the maximum concentration, which is 100 mg L À1 .…”
Section: Evaluation Of Acute and Chronic Toxicity Effects Of Agnps-ewmentioning
confidence: 99%
“…On the basis of these ndings, it was demonstrated that the concentration range from 10 to 100 mg L À1 of AgNPs-EW did not cause any signicant acute and chronic toxic effects on the reproductive traits, namely the fecundity, hatchability, viability, duration of development, and pigmentation of Drosophila. We compared these ndings with previously reported AgNPs toxicity studies on Drosophila and summarize the results in Table 2, [58][59][60][61][62] which clearly shows that AgNPs toxicity is based on the capping agents used for nanoparticles synthesis, size, and dose. Based on our literature study, we understand that this is the rst report of AgNPs-EW having no acute and chronic toxicity effects on Drosophila at the maximum concentration, which is 100 mg L À1 .…”
Section: Evaluation Of Acute and Chronic Toxicity Effects Of Agnps-ewmentioning
confidence: 99%
“…One common form of lysosomal dysfunction that has been associated with nanomaterial treatments is increased lysosomal membrane permeabilization (LMP). Proton pump inhibitors, such as bafilomycin A1, that block autophagic flux predispose cells to LMP, triggering apoptosis through the LMP-induced release of pro-apoptosis mediators such as cathepsin [45]. LMP is a recognized cell death mechanism that can result in mitochondrial membrane permeabilization through several mechanisms, including lysosomal-iron mediated oxidative stress and the release of cathepsin or other lysosomal associated hydrolases [45].…”
Section: Autophagy Dysfunction As a Cell Toxicity Mechanismmentioning
confidence: 99%
“…Proton pump inhibitors, such as bafilomycin A1, that block autophagic flux predispose cells to LMP, triggering apoptosis through the LMP-induced release of pro-apoptosis mediators such as cathepsin [45]. LMP is a recognized cell death mechanism that can result in mitochondrial membrane permeabilization through several mechanisms, including lysosomal-iron mediated oxidative stress and the release of cathepsin or other lysosomal associated hydrolases [45]. As lysosomal dysfunction has been involved in disease pathogenesis, the association of nanoparticle exposure and lysosomal dysfunction may have relevance to nanomaterial-induced toxicity levels, especially chronic toxicity.…”
Section: Autophagy Dysfunction As a Cell Toxicity Mechanismmentioning
confidence: 99%
See 1 more Smart Citation
“…Delays in the development from egg-toadult have been detected when eggs or larvae were exposed (Gorth et al 2011;Philbrook et al 2011;Vecchio et al 2013;Han et al 2014;Vega-Alvarez et al 2014;Raj et al 2017a). Interestingly, these effects were translated to the emerged adults who present shortened life span, mating success decrease, and less fertility (Key et al 2011;Panacek et al 2011;Posgai et al 2011;Armstrong et al 2013;Tian et al 2013;Mao et al 2018). The observed loss of fertility was associated with a decreased number of germline stem cells (Ong et al 2016), and also a reduced pigmentation was observed in adults, mainly depending on AgNPs concentration (Panacek et al 2011;Avalos et al 2015;Phatak et al 2016).…”
Section: Introductionmentioning
confidence: 99%